Revisiting the Evidence on the Cyclicality of Fiscal Policy across the World - Carneiro, Francisco G.; Garrido, Leonardo (World Bank, Washington, DC, 2016)
A large and growing literature has argued that industrialized and developing countries behave very differently in relation to their fiscal policy stances over the business cycle. In this paper, the authors provide new evidence on the cyclicality of fiscal policy across industrialized and developing countries. The authors sample includes 180 countries, of which 134 are developing countries and 46 are high income countries over the period 1980-2012. The authors follow the methodology of Frankel et al. (2013) but at the same time introduce three innovations to the empirical approach. This paper is organized as follows : After Introduction, Section two discusses issues associated with the choice of filter to smooth the proxy variable for fiscal cyclicality while Section three estimates our own Graduating Class under different filtering methods and a country-specific approach to split the sample into two sub-periods. Section four presents an analysis of how the countries in our sample behave over the business cycle. Section five discusses our findings on the empirical determinants of fiscal cyclicality while Section six explores endogeneity issues. Section 7 presents concluding remarks confirming earlier findings in the literature on the causal link between institutional quality and a less pro-cyclical fiscal stance and suggesting policy directions that could be useful to countries interested in strengthening their fiscal positions and becoming better equipped to adopt counter-cyclical fiscal policies